Negative electrode structure and all-solid-state battery comprising same

By setting a composite sulfide or polymer film transition layer with a thickness of ≤5μm between the metal negative electrode and the halide solid electrolyte of the all-solid state battery, the stability problem between the halide solid electrolyte and the metal negative electrode is solved, and higher energy is achieved Density and cycling performance enhance battery safety.

CN119447179AActive Publication Date: 2025-02-14HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411422274.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

When using halide solid electrolytes, existing all-solid state batteries have stability problems with metal negative electrodes, resulting in the need to increase the sulfide SSE transition layer with a larger thickness, which increases the mass, volume and cost of the battery, and reduces the energy density. and performance.

Method used

A composite sulfide film or polymer film with a thickness of ≤5μm is provided as a transition layer between the metal negative electrode and the halide solid electrolyte to form an integrated negative electrode structure, and avoid direct contact between the sulfide SSE particles and the halide solid electrolyte and the metal negative electrode .

Benefits of technology

Improves interface stability and battery cycling performance, significantly reduces the battery's volume and quality, improves energy density, and enhances the battery's safety, allowing it to directly match with high voltage positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447179A_ABST
    Figure CN119447179A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode structure and an all-solid-state battery containing the same, the negative electrode structure comprises a halide solid electrolyte and a metal negative electrode, and a thin film layer with the thickness less than or equal to 5 microns is arranged between the halide solid electrolyte and the metal negative electrode; the thin film layer is a composite sulfide thin film or a polymer thin film formed by in-situ curing. According to the negative electrode structure, the uniform thin film layer with high ionic conductivity, thin thickness and certain mechanical strength is arranged between the halide solid electrolyte and the metal negative electrode, and the thin film layer, the metal negative electrode and the halide solid electrolyte are assembled into the integrated negative electrode structure, so that the halide solid electrolyte and the negative electrode can be completely separated, and an interface reaction is inhibited; the interface impedance is reduced, a relatively thick sulfide transition layer is avoided, and the safety of the battery can be improved while a high-voltage positive electrode material can be matched, so that the energy density and the performance of the all-solid-state battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to a negative electrode structure, and an all-solid-state battery containing the negative electrode structure. Background Art

[0002] In secondary batteries, traditional organic electrolytes pose safety risks due to their flammability, so the current research direction is to use safer solid electrolytes (SSE) to replace organic electrolytes. All-solid-state batteries are not only safer, but also compatible with higher voltage positive electrode materials and low voltage metal negative electrode materials, thus having higher energy density.

[0003] The solid electrolytes used in common solid-state batteries are mainly some lithium / sodium ion oxides, sulfides and borohydrides. These solid electrolyte materials all show high ionic conductivity. Among them, sulfides have the highest ionic conductivity (e.g. Na 3 PS 4 , Li 6 PS 5 Cl, ion conductivity is 0.1~10mS·cm -1 ), which is close to or even higher than organic liquid electrolytes, but its chemical and electrochemical stability is poor, and the battery capacity decays rapidly when matched with a high-voltage positive electrode. 3 Zr 2 Si 2 PO 12 Etc., they are hard and not easily deformed, resulting in poor physical contact with electrode materials, which seriously hinders the transmission of lithium / sodium ions at the interface and leads to the deterioration of battery performance.

[0004] Compared with oxide solid electrolytes and sulfide solid electrolytes, halide solid electrolytes have certain advantages and promotion prospects due to their high voltage stability and interface compatibility with positive electrode materials. However, since existing halide SSEs have stability issues with lithium / sodium metal anodes, a sulfide SSE transition layer is usually added between the metal anode and the halide SSE when assembling all-solid-state batteries. 3 PS 4etc., thereby avoiding contact between the two. Although the presence of this transition layer can solve the problem of stability between the halide SSE and the lithium / sodium metal negative electrode, the thickness of the transition layer is usually too thick (generally 30 to 100 μm), on the one hand, it will increase the mass, volume and cost of the all-solid-state battery; on the other hand, it will greatly reduce the energy density of the all-solid-state battery, making it impossible to fully utilize the advantages of the all-solid-state battery. In addition, the added sulfide SSE transition layer and the halide SSE used also have certain interface stability risks (there are certain side reactions at the interface), which will bring additional interface impedance and reduce the performance of the all-solid-state battery. Summary of the invention

[0005] In view of this, the primary purpose of the present invention is to provide a negative electrode structure, which arranges a uniform thin film layer with high ionic conductivity, thin thickness and certain mechanical strength between the metal negative electrode and the halide solid electrolyte layer, and assembles the metal negative electrode and the halide solid electrolyte into an integrated negative electrode structure. The integrated negative electrode can be directly matched with a high-voltage positive electrode material to improve the performance of the all-solid-state battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention first provides a negative electrode structure, comprising a halide solid electrolyte and a metal negative electrode, wherein a thin film layer with a thickness of ≤5 μm is provided between the halide solid electrolyte and the metal negative electrode;

[0008] The film layer is a composite sulfide film or a polymer film formed by in-situ curing, and the composite sulfide film is composited by a sulfide solid electrolyte and a polymer solid electrolyte.

[0009] In a further embodiment, the film layer has a thickness of 0.2 to 5 μm.

[0010] In a further embodiment, the film layer has a thickness of 0.5 to 1.5 μm.

[0011] In a further embodiment, the sulfide solid electrolyte is Li 6 PS 5 Cl, Li 10 G 2 S 11 , Li 7 S 3 P 11 , Li 3 PS 4 ;Na 3 PS 4 、Na 2.9 PS 3.9 Cl 0.1 、Na 4 P2 S 7 、Na 3 Sb 4 One or a combination of two or more.

[0012] In a further embodiment, the polymer solid electrolyte is prepared from a polymer and an electrolyte salt.

[0013] In a further embodiment, the molar ratio of the polymer to the electrolyte salt is 8:1 to 20:1.

[0014] In a further embodiment, the polymer is PEO, PVDF, CMC, PVDF-HFP or PMMA.

[0015] In a further embodiment, the electrolyte salt is a lithium salt or a sodium salt.

[0016] In a further embodiment, the lithium salt is LiTFSI, LiFSI, LiPF 6 , LiDFOB, LiBOB or a combination of two or more thereof; and / or the sodium salt is NaTFSI, NaFSI, NaPF 6 、NaClO 4 One or more of the

[0017] In a further embodiment, in the composite sulfide film, the content of the polymer solid electrolyte is 1 wt% to 20 wt%.

[0018] In a further embodiment, the content of the polymer solid electrolyte in the composite sulfide film is 3wt% to 10wt%.

[0019] In a further embodiment, the halide solid electrolyte is a lithium ion halide solid electrolyte or a sodium ion halide solid electrolyte;

[0020] And / or, the metal negative electrode is metal lithium, metal sodium or an alloy containing metal lithium or sodium.

[0021] In a further embodiment, the thickness of the halide solid electrolyte is 2 to 20 μm.

[0022] In a further embodiment, the thickness of the halide solid electrolyte is 5 to 10 μm.

[0023] The present invention further provides a method for preparing the negative electrode structure as described above, comprising the following steps:

[0024] forming a thin film layer;

[0025] After assembling the halide solid electrolyte, thin film layer and metal negative electrode, they are pressed under high pressure of 200MPa to 370MPa to form an integrated negative electrode structure.

[0026] In a further embodiment, the film layer is a composite sulfide film.

[0027] In a further embodiment, the film layer is a polymer film, which is prepared as follows:

[0028] Preparing a prepolymer precursor solution, wherein the prepolymer precursor solution contains a polymerizable monomer, an electrolyte salt and an initiator;

[0029] The supporting film is placed on the metal negative electrode, the prepolymer precursor liquid is injected, and in-situ curing is performed to obtain a polymer film.

[0030] In a further embodiment, the polymerizable monomer is at least one of vinylene carbonate, vinyl ethylene carbonate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl methacrylate, n-butyl acrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A dimethacrylate, polyethylene glycol dimethacrylate, acrylic acid, polyethylene glycol dimethyl ether, polyethylene glycol diglycidyl ether, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;

[0031] and / or, the electrolyte salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium bisoxalate borate, lithium difluorooxalate borate, lithium difluorophosphate, lithium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisfluorosulfonyl imide, sodium bisoxalate borate, sodium difluorooxalate borate, sodium difluorophosphate, and sodium perchlorate;

[0032] And / or, the initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, azobisisobutylcyanoformamide, azobiscyclohexylcarbonitrile, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, dibenzoyl peroxide, dodecyl peroxide, diisopropyl peroxydicarbonate, and methyl ethyl ketone peroxide.

[0033] The present invention further provides an all-solid-state battery, comprising the negative electrode structure as described above or the negative electrode structure prepared by the preparation method as described above.

[0034] Beneficial effects of the present invention:

[0035] The integrated negative electrode structure provided in the present invention uses a thin film layer with a thickness of ≤5μm as a transition layer to avoid direct contact between sulfide SSE particles and halide solid electrolyte and metal negative electrode, thereby improving the interface stability and battery cycle performance. In addition, since the traditional thicker sulfide SSE is not used as a transition layer, the volume and mass of the all-solid-state battery are significantly reduced, and the energy density of the all-solid-state battery is greatly improved. And the integrated negative electrode can be directly matched with the high-voltage positive electrode material, while improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the negative electrode structure in a preferred embodiment of the present invention.

[0037] Figure 2 These are the impedance test results of the composite sulfide films prepared in Examples 1 and 7.

[0038] Figure 3 The test results of the cycle performance of the all-solid-state battery in Example 1 are shown. DETAILED DESCRIPTION

[0039] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0041] The first aspect of the present invention provides a negative electrode structure, the structure diagram is as follows Figure 1 As shown in , the negative electrode structure is an integrated negative electrode structure, which is composed of a halide solid electrolyte and a metal negative electrode, and a thin film layer arranged between the halide solid electrolyte and the metal negative electrode.

[0042] The halide solid electrolyte described herein may be a conventional type in the art, preferably a halide solid electrolyte with high ionic conductivity to ensure the performance of the all-solid-state battery. In some specific embodiments of the present invention, the composition of the halide SSE is A y M x B 1-x X z , wherein A is Li or Na, M is at least one of La, Sm, Ta, Al, Yb, Ho, Er, B is at least one of Y, In, Sc, Zr, Er, Ti, Hf, X is Cl or Br; 0≤x≤1, 2≤y≤3, z≤6. Specific examples include Li3 InCl 6 , Li 3 YC 6 , Li 3 E 6 , Li 2 ZrCl 6 、Na 2 ZrCl 6 、Na 2.25 Y 0.25 Zr 0.75 Cl 6 、Na 0.7 La 0.7 Zr 0.3 Cl 4 、NaAlCl 4 , but not limited thereto. The thickness of the specific halide solid electrolyte is not particularly limited and can be within the range in the art. In some specific embodiments of the present invention, it is preferably 2 to 20 μm, for example, it can be any value among 2 μm, 5 μm, 8 μm, 10 μm, 14 μm, 16 μm, 18 μm, and 20 μm. Preferably, the thickness of the halide solid electrolyte is any value among 5 to 10 μm.

[0043] The metal negative electrode described herein is selected according to the specific battery type. When the battery is a lithium-ion battery, the metal negative electrode is metal lithium or an alloy containing metal lithium; when the battery is a sodium-ion battery, the metal negative electrode is metal sodium or an alloy containing metal sodium. The specific thickness of the metal negative electrode can adopt the conventional thickness in the art, such as ≤10μm, preferably 5 to 7μm, for example, 5μm, 6μm, 7μm, etc.

[0044] The integrated negative electrode structure of the present invention is achieved by setting a thin film layer between the halide SSE and the metal negative electrode. The thin film layer has a uniform composition, high ionic conductivity, a thin thickness and a certain mechanical strength, which can completely isolate the halide SSE and the metal negative electrode, thereby improving the performance of the all-solid-state battery.

[0045] The thickness of the thin film layer described herein is ≤5 μm, preferably, 1-5 μm, for example, any value of 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0046] The film layer described herein is a composite sulfide film in some embodiments, and the composite sulfide film is composed of a sulfide solid electrolyte and a polymer solid electrolyte, wherein the content of the polymer solid electrolyte is 1wt% to 20wt%, for example, it can be any value among 1wt%, 2wt%, 3wt%, 5wt%, 8wt%, 10wt%, 14wt%, 15wt%, 17wt%, 20wt%, preferably, the content of the polymer solid electrolyte is 3wt% to 10wt%. The sulfide solid electrolyte provides high ionic conductivity, while the polymer solid electrolyte acts as a binder on the one hand and provides another part of the ion transmission path on the other hand.

[0047] The sulfide solid electrolyte can be a conventional type in the art, preferably Li 6 PS 5 Cl, Li 10 G 2 S 11 , Li 7 S 3 P 11 , Li 3 PS 4 ;Na 3 PS 4 、Na 2.9 PS 3.9 Cl 0.1 、Na 4 P 2 S 7 、Na 3 Sb 4 One or a combination of more than two of the above, but not limited thereto, can be selected according to the battery type and actual needs.

[0048] The polymer solid electrolyte is prepared from a polymer and an electrolyte salt. Specifically, the polymer may be PEO, PVDF, CMC, PVDF-HFP or PMMA. The electrolyte salt may be a lithium salt or a sodium salt depending on the type of battery. In some specific embodiments of the present invention, the electrolyte salt is a lithium salt, such as LiTFSI, LiFSI, LiPF 6 , LiDFOB, LiBOB or a combination of two or more thereof; in other specific embodiments of the present invention, the electrolyte salt is a sodium salt, such as NaTFSI, NaFSI, NaPF 6 、NaClO 4 One or a combination of two or more of the above. But it is not limited to this.

[0049] In some specific embodiments of the present invention, the molar ratio of the polymer to the electrolyte salt is 8:1 to 20:1, for example, it can be any ratio of 8:1, 9:1, 10:1, 12:1, 15:1, 16:1, 18:1, and 20:1, preferably 20:1.

[0050] In other embodiments, the thin film layer described herein is a polymer thin film formed by in-situ curing, which can be formed by injecting a prepolymer precursor liquid into the contact surface between the support film and the metal negative electrode and performing an in-situ curing reaction.

[0051] The second aspect of the present invention provides a method for preparing the negative electrode structure according to the first aspect of the present invention, comprising the following steps:

[0052] forming a thin film layer;

[0053] After assembling the halide solid electrolyte, thin film layer and metal negative electrode, they are pressed under high pressure of 200MPa to 370MPa to form an integrated negative electrode structure.

[0054] In some specific embodiments of the present invention, the film layer is a composite sulfide film, which is prepared by mixing a sulfide solid electrolyte and a polymer solid electrolyte and then casting the mixture. Preferably, the sulfide solid electrolyte is prepared by high-energy ball milling.

[0055] In some other specific embodiments of the present invention, the film layer is a polymer film, which can be formed by in-situ curing by casting, spin coating, etc. In some specific implementation cases of the present invention, its preparation includes the following steps:

[0056] Preparing a prepolymer precursor solution, wherein the prepolymer precursor solution contains a polymerizable monomer, an electrolyte salt and an initiator;

[0057] Placing a support film on a metal negative electrode, injecting the prepolymer precursor solution, and in-situ curing to obtain a polymer film;

[0058] Among them, the polymerizable monomer can be at least one of vinylene carbonate, vinyl ethylene carbonate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl methacrylate, n-butyl acrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A dimethacrylate, polyethylene glycol dimethacrylate, acrylic acid, polyethylene glycol dimethyl ether, polyethylene glycol diglycidyl ether, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate.

[0059] Further, the electrolyte salt is a conventional lithium salt or sodium salt commonly used in the art, and specific examples include lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium bisoxalate borate, lithium difluorooxalate borate, lithium difluorophosphate, lithium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisfluorosulfonyl imide, sodium bisoxalate borate, sodium difluorooxalate borate, sodium difluorophosphate and sodium perchlorate, but are not limited thereto. The specific type can be selected according to the type of battery, etc., and the specific concentration can be the conventional concentration in the art, such as 0.2 to 3.0 mol / L.

[0060] Further, the initiator can be adapted according to the specific type of polymerizable monomer, and specific examples include at least one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, azobisisobutylcyanoformamide, azobiscyclohexylcarbonitrile, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, dibenzoyl peroxide, dodecyl peroxide, diisopropyl peroxydicarbonate, and methyl ethyl ketone peroxide, but is not limited thereto. The amount of the initiator added can be selected according to actual needs, preferably 0.1wt% to 10wt%.

[0061] In addition, it is understood that most polymerizable monomers can be used as solvents. Additional solvents such as EC, PC, EMC, DEC, DMC, VC or FEC can be added as needed, and these additional solvents can also be used as plasticizers to further improve the performance of the film layer.

[0062] It is understandable that the preparation of the thin film layer in the present invention is not limited to the above preparation method, and any method in the art that can prepare the thin film layer in the present invention is applicable to the preparation of the negative electrode structure in the present invention.

[0063] The third aspect of the present invention provides an all-solid-state battery, comprising the negative electrode structure as described in the first aspect of the present invention or the negative electrode structure prepared by the preparation method described in the first aspect of the present invention.

[0064] It is understandable that the positive electrode and other materials in the all-solid-state battery can adopt conventional compositions in the art and will not be elaborated in detail here.

[0065] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0066] Example 1

[0067] This embodiment provides a negative electrode structure in which the film layer is a composite sulfide film and the preparation of an all-solid-state battery based on the negative electrode structure, and the specific steps are as follows:

[0068] 1. Preparation of composite sulfide film Na 3 PS 4 -PEO-NaTFSI

[0069] In an inert atmosphere, sodium sulfide (Na 2 S) and phosphorus pentasulfide (P 2 S 5 ) sealed in zirconium oxide (ZrO 2 ) ball mill, milled in a planetary ball mill at 500 rpm for 10 h, and then annealed at 270 ° C for 1 h to obtain Na 3 PS 4 .

[0070] 970 mg Na 3 PS 4 30 mg PEO-NaTFSI (EO / Na = 20:1 molar ratio) was added to acetonitrile solvent (ACN), stirred at 60 ° C for 24 h, and then formed into a film by casting, dried at 80 ° C for 2 h, and finally hot-pressed at 200 ° C to obtain a Na film with a thickness of 3 μm. 3 PS 4 -PEO-NaTFSI (3wt%) composite sulfide film.

[0071] 2. Assembling all-solid-state batteries

[0072] Positive electrode: The positive electrode active material sodium vanadium phosphate (Na 3 V 2 (PO4) 3 ), and Na 0.7 La 0.7 Zr 0.3 Cl 4 (NLZC) and conductive agent SP were mixed in a mass ratio of 50:50:3, and then ball-milled in a planetary ball mill at a speed of 200 rpm for 30 min using a stainless steel ball mill to obtain a positive electrode powder, which was then pressed to obtain a composite positive electrode.

[0073] Negative electrode: Sodium metal and tin metal were mixed in a stainless steel ball mill at a molar ratio of 2:1, and ball-milled in a planetary ball mill at 300 rpm for 20 h to obtain a sodium-tin alloy, which was then pressed to obtain a negative electrode.

[0074] Halide SSE: Sodium chloride (NaCl), lanthanum chloride (LaCl 3 ) and zirconium chloride (ZrCl 4) were mixed in a molar ratio of 0.7:07:0.3, and then sealed in zirconium oxide (ZrO 2 ) in a ball mill jar and milled in a planetary ball mill at 550 rpm for 10 h to obtain Na 0.7 La 0.7 Zr 0.3 Cl 4 Precursor; after annealing the precursor at 400 ° C for 2 hours, it is ball-milled again for 5 to 10 hours to obtain halide SSE, Na 0.7 La 0.7 Zr 0.3 Cl 4 .

[0075] The halide SSE, composite sulfide film and metal negative electrode were assembled in a polytetrafluoroethylene mold with a diameter of 12 mm and maintained at a pressure of 370 MPa for 10 minutes to form an integrated negative electrode structure; the integrated negative electrode structure and the composite positive electrode were successively loaded into the mold under a pressure of 370 MPa to form an all-solid-state battery.

[0076] Example 2

[0077] The preparation of the negative electrode structure in this embodiment is the same as that in Example 1, except that the polymer solid electrolyte in the composite sulfide film is PVDF-HFP-NaTFSI. Other process conditions and the preparation of the all-solid-state battery are the same as in Example 1.

[0078] Example 3

[0079] The preparation of the negative electrode structure in this embodiment is the same as that in Example 1, except that the polymer solid electrolyte in the composite sulfide film is PEO-NaFSI. Other process conditions and the preparation of the all-solid-state battery are the same as in Example 1.

[0080] Example 4

[0081] The preparation of the negative electrode structure in this embodiment is the same as that in Example 1. The only difference is that the sulfide solid electrolyte in the composite sulfide film is Na 2.9 PS 3.9 Cl 0.1 The other process conditions and the preparation of the all-solid-state battery are the same as those in Example 1.

[0082] Example 5

[0083] The preparation of the negative electrode structure in this embodiment is the same as that in Example 1, except that the content of the polymer solid electrolyte in the composite sulfide film is 10 wt %. Other process conditions and the preparation of the all-solid-state battery are the same as those in Example 1.

[0084] Example 6

[0085] The preparation of the negative electrode structure in this embodiment is the same as that in Example 1, except that the content of the polymer solid electrolyte in the composite sulfide film is 5 wt %. Other process conditions and the preparation of the all-solid-state battery are the same as those in Example 1.

[0086] Example 7

[0087] The preparation of the composite sulfide film in this embodiment is as follows:

[0088] 1. Preparation of composite sulfide film Li 6 PS 5 Cl-PEO-LiTFSI

[0089] In an inert atmosphere, lithium chloride (LiCl), lithium sulfide (Li 2 S) and phosphorus pentasulfide (P 2 S 5 ) sealed in zirconium oxide (ZrO 2 ) in a ball mill jar, and milled in a planetary ball mill at a speed of 500 rpm for 20 hours, and then annealed at 500 ° C for 10 hours to obtain Li 6 PS 5 Cl.

[0090] 950 mg Li 6 PS 5 Cl and 50 mg PEO-LiTFSI (EO / Na = 20:1 molar ratio) were added to acetonitrile solvent (ACN), stirred at 60 ° C for 24 h, and then formed into a film by casting, dried at 80 ° C for 2 h, and finally hot-pressed at 200 ° C to obtain a Li film with a thickness of 5 μm. 6 PS 5 Cl-PEO-LiTFSI (5wt%) composite sulfide film.

[0091] 2. Assembling all-solid-state batteries

[0092] Positive electrode: The positive electrode active material is lithium cobalt oxide (LiCoO 2 ), with halide Li 3 InCl 6 and the conductive agent SP in a mass ratio of 70:30:1, and then ball-milled in a planetary ball mill at a speed of 200 rpm for 30 min using a stainless steel ball mill to obtain a positive electrode powder, which was then pressed to obtain a composite positive electrode.

[0093] Negative electrode: Metallic lithium and metallic tin were mixed in a stainless steel ball mill at a molar ratio of 2:1, and ball-milled in a planetary ball mill at 300 rpm for 20 h to obtain a lithium-tin alloy, which was then pressed to obtain a negative electrode.

[0094] Halide SSE: Lithium chloride (LiCl), indium chloride (InCl 3 )3:1 molar ratio, and then sealed in zirconium oxide (ZrO 2 ) in a ball mill jar and milled in a planetary ball mill at 550 rpm for 10 h to obtain Li 3 InCl 6 Halide SSE.

[0095] The halide SSE, 5μm Li 6 PS 5 The Cl-PEO-LiTFSI composite sulfide film and the metal negative electrode were assembled in a polytetrafluoroethylene mold with a diameter of 12 mm and maintained at a pressure of 370 MPa for 10 minutes to form an integrated negative electrode; the integrated negative electrode and the composite positive electrode were successively loaded into the mold under a pressure of 370 MPa to assemble into an all-solid-state battery.

[0096] Example 8

[0097] This embodiment provides a negative electrode structure in which the thin film layer is a polymer thin film and the preparation of an all-solid-state battery based on the negative electrode structure, and the specific steps are as follows:

[0098] 1. Preparation of prepolymer precursor solution:

[0099] The liquid organic solvent vinylene carbonate, the electrolyte salt sodium hexafluorophosphate, the initiator azobisisobutyronitrile, the additive succinonitrile and the functional additive N-methyl-N-(trimethylsilyl)trifluoroacetamide are fully mixed and stirred to obtain a prepolymer precursor solution.

[0100] Wherein, taking the liquid organic solvent as the measurement standard, the concentration of sodium hexafluorophosphate is 1 mol / L; the content of azobisisobutyronitrile is 2 wt %; the content of succinonitrile is 10 wt %; and the content of N-methyl-N-(trimethylsilyl)trifluoroacetamide is 2 wt %.

[0101] 2. Preparation of integrated negative electrode

[0102] According to the liquid lithium battery assembly method, in an argon-protected glove box, a glass fiber separator was placed on the sodium metal negative electrode, and a prepolymer precursor solution was injected and heated at 55°C for 12h to form a GPE polymer film with a thickness of 5μm;

[0103] After assembling the halide SSE, gel-gel polymer film and sodium metal anode, the pressure was maintained at 370 MPa for 10 min to obtain an integrated anode.

[0104] 3. Assembling all-solid-state batteries

[0105] After assembling the composite positive electrode and the integrated negative electrode, they are assembled into an all-solid-state battery under a pressure of 370MPa.

[0106] The compositions of the composite positive electrode, halide SSE and metal negative electrode in the all-solid-state battery are the same as those in Example 1.

[0107] Example 9

[0108] The preparation of the negative electrode structure in this embodiment is the same as that in embodiment 8, except that the initiator in the polymer film is azobisisovaleronitrile. Other process conditions and the preparation of the all-solid-state battery are the same as those in embodiment 8.

[0109] Example 10

[0110] The preparation of the negative electrode structure in this embodiment adopts the same implementation method as that of Example 8, with the only difference being that the electrolyte salt in the polymer film is lithium hexafluorophosphate, and in addition, the negative electrode adopts a metallic lithium negative electrode.

[0111] The prepared negative electrode structure is combined with the halide Li 3 InCl 6 , lithium cobalt oxide positive electrode to form an all-solid-state battery, in which the halide Li 3 InCl 6 , the preparation of the lithium cobalt oxide positive electrode is the same as in Example 7.

[0112] Comparative Example 1

[0113] The preparation of the all-solid-state battery in this comparative example adopts the same method as that in Example 1, except that the composite sulfide film in Example 1 is replaced by a sulfide Na2O3 film with a thickness of 50 μm. 3 PS 4 .

[0114] Performance Testing

[0115] The all-solid-state batteries prepared in the examples and comparative examples were cycled for 70 cycles at 30° C. to test their electrochemical properties. The test results are shown in Table 1.

[0116] Table 1 All-solid-state battery performance test

[0117] Cathode Materials First cycle discharge specific capacity Capacity retention rate after 70 cycles Example 1 NVP 115mAh / g 88% Example 2 NVP 110mAh / g 85% Example 3 NVP 111mAh / g 87% Example 4 NVP 105mAh / g 90% Example 5 NVP 115mAh / g 95% Example 6 NVP 108mAh / g 92% Example 7 LCO 140mAh / g 90% Example 8 NVP 115mAh / g 90% Example 9 NVP 101mAh / g 95% Example 10 LCO 180mAh / g 84% Comparative Example 1 NVP 110mAh / g 80%

[0118] It can be seen from the test results in Table 1 that the all-solid-state battery prepared using the integrated negative electrode of the present invention has excellent electrochemical performance. Among them, the battery of Example 10 is charged to 4.5V, and the first cycle discharge specific capacity can reach 180mAh / g, indicating that the integrated negative electrode of the present invention can be directly matched with the high voltage positive electrode and has excellent performance.

[0119] also, Figure 2Graphs 2 and 3 show the impedance test results of the composite sulfide films prepared in Examples 1 and 7, which are 330Ω and 342Ω, respectively. Figure 3 The figure shows the cycle performance test results of the all-solid battery in Example 1. After 70 cycles, the discharge capacity of the all-solid battery is 102 mAh / g, and the capacity retention rate is 88%.

[0120] The above examples demonstrate that the integrated negative electrode structure of the present invention avoids the use of a sulfide SSE transition layer, so that the interface impedance between interfaces is small, the assembled all-solid-state battery has a high energy density and excellent cycle performance, and can be directly matched with a high-voltage positive electrode.

[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A negative electrode structure, characterized in that: It comprises a halide solid electrolyte and a metal negative electrode, wherein a thin film layer with a thickness of ≤5 μm is provided between the halide solid electrolyte and the metal negative electrode; The film layer is a composite sulfide film or a polymer film formed by in-situ curing, and the composite sulfide film is composited by a sulfide solid electrolyte and a polymer solid electrolyte.

2. The negative electrode structure according to claim 1, characterized in that: The thickness of the film layer is 0.2 to 5 μm; Preferably, the film layer has a thickness of 0.5 to 1.5 μm.

3. The negative electrode structure according to claim 1, characterized in that: The sulfide solid electrolyte is Li6PS5Cl, Li7S3P 11 、Li3PS4、Li 10 GeP2S 11 ; Na3PS4, Na 2.9 PS 3.9 Cl 0.1 , Na4P2S7, Na3SbS4 or a composite of two or more thereof.

4. The negative electrode structure according to claim 1, characterized in that: In the composite sulfide film, the content of the polymer solid electrolyte is 1wt% to 20wt%; Preferably, in the composite sulfide film, the content of the polymer solid electrolyte is 3wt% to 10wt%.

5. The negative electrode structure according to claim 1 or 4, characterized in that: The polymer solid electrolyte is prepared from a polymer and an electrolyte salt; Preferably, the molar ratio of the polymer to the electrolyte salt is 8:1 to 20:1; Preferably, the polymer is PEO, PVDF, CMC, PVDF-HFP or PMMA; Preferably, the electrolyte salt is a lithium salt or a sodium salt; Preferably, the lithium salt is one or a combination of two or more of LiTFSI, LiFSI, LiPF6, LiDFOB, and LiBOB; and / or, the sodium salt is one or a combination of two or more of NaTFSI, NaFSI, NaPF6, and NaClO4.

6. The negative electrode structure according to claim 1, characterized in that: The halide solid electrolyte is a lithium ion halide solid electrolyte or a sodium ion halide solid electrolyte; And / or, the metal negative electrode is metal lithium, metal sodium or an alloy containing metal lithium or sodium; Preferably, the thickness of the halide solid electrolyte is 2 to 20 μm; Preferably, the thickness of the halide solid electrolyte is 5 to 10 μm.

7. A method for preparing a negative electrode structure according to any one of claims 1 to 6, characterized in that: The following steps are involved: forming a thin film layer; After assembling the halide solid electrolyte, thin film layer and metal negative electrode, they are pressed under high pressure of 200MPa to 370MPa to form an integrated negative electrode structure.

8. The preparation method according to claim 7, characterized in that: The film layer is a composite sulfide film.

9. The preparation method according to claim 7, characterized in that: The film layer is a polymer film, which is prepared as follows: Preparing a prepolymer precursor solution, wherein the prepolymer precursor solution contains a polymerizable monomer, an electrolyte salt and an initiator; Placing a support film on a metal negative electrode, injecting the prepolymer precursor solution, and in-situ curing to obtain a polymer film; Preferably, the polymerizable monomer is at least one of vinylene carbonate, vinyl ethylene carbonate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl methacrylate, n-butyl acrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated bisphenol A dimethacrylate, polyethylene glycol dimethacrylate, acrylic acid, polyethylene glycol dimethyl ether, polyethylene glycol diglycidyl ether, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate; and / or, the electrolyte salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium bisoxalate borate, lithium difluorooxalate borate, lithium difluorophosphate, lithium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium bisfluorosulfonyl imide, sodium bisoxalate borate, sodium difluorooxalate borate, sodium difluorophosphate, and sodium perchlorate; And / or, the initiator is at least one of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, azobisisobutylcyanoformamide, azobiscyclohexylcarbonitrile, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, dibenzoyl peroxide, dodecyl peroxide, diisopropyl peroxydicarbonate, and methyl ethyl ketone peroxide.

10. An all-solid-state battery, characterized in that: Contains the negative electrode structure as described in any one of claims 1 to 6 or is prepared by the preparation method as described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Composite positive electrode, solid-state lithium ion secondary battery, and electric device

    CN115172653A

  • Composite solid electrolyte film and preparation method and application thereof

    CN115458801A

  • Solid electrolyte material, preparation method and electrode

    CN116315052A

  • All-solid-state secondary battery and preparation method thereof

    CN117039133A

  • Composite solid electrolyte, preparation method thereof and lithium ion battery

    CN117976967A

Cited By

  • Lithium metal negative electrode material of solid-state battery, production process of lithium metal negative electrode material and solid-state battery

    CN120048891A